2020
DOI: 10.1111/tbed.13854
|View full text |Cite
|
Sign up to set email alerts
|

The wildlife‐livestock interface on extensive free‐ranging pig farms in central Spain during the “montanera” period

Abstract: The effective management of shared pathogens between wild ungulates and livestock requires the understanding of the processes of interaction between them. In this work, we studied the interspecific frequency of interaction (ifreq) and its spatiotemporal pattern between wild and domestic ungulates that coexist in free-ranging farms. For this purpose, 6 red deer, 6 wild boar, 8 Iberian pigs and 3 cattle were monitored using GPS devices during the "montanera" period (the period in which Iberian pigs are maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…High contact rates between Iberian swine and human handlers also facilitate bidirectional transmission of other pathogens ( Wiethoelter et al. 2015 ; Roxana et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…High contact rates between Iberian swine and human handlers also facilitate bidirectional transmission of other pathogens ( Wiethoelter et al. 2015 ; Roxana et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, these interactions are detected by the observation of damages in the fence or the observation of crossbred offspring a few weeks later. Further studies using ecological tools (camera traps and /or telemetry devices with proximity loggers) should be implemented in order to confirm and better quantify wild boar incursions in the farms and document the potential occurrence of wild boar-domestic pig interactions in the study area (Kukielka et al, 2013;Triguero-Ocaña et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These two parallel developments facilitate an increasing occurrence of interactions between domestic pigs and wild boars, which can have several sanitary and environmental consequences. This phenomenon is widespread in most of the distribution area of Sus scrofa in Eurasia and this topic is raising increased international attention with the global spread of African swine fever in Europe and Asia, which can facilitate the circulation of this virus and other pathogens at the wildlife-livestock interface (Boklund et al, 2020;Jori, Payne, Stahl, Nava, & Rossi, 2018;Triguero-Ocaña et al, 2021). Several studies found in the literature have assessed the frequency and intensity of wild boar/domestic pig interactions from the ecological or behavioral perspective in the USA (Wyckoff, Henke, Campbell, Hewitt, & VerCauteren, 2009) and Europe (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Livestock exposure probability depends on contacts between wildlife and livestock. Specific studies to characterize the wildlife-livestock interface use different methods such as questionnaires to stakeholders ( Meunier et al, 2017 ), telemetric monitoring of wildlife ( Triguero-Ocaña et al, 2020 ), or rely on data analysis by modelling ( Barasona et al, 2014 ) or risk factor identification ( Sichewo et al, 2020 ). A systematic review has highlighted the wide variation and lack of consensus in the definitions of direct and indirect contacts between wild and farm animals ( Bacigalupo et al, 2020 ).…”
Section: Risk Assessment Of Emergencementioning
confidence: 99%